Effects of Capital Structure on Profitability of the Manufacturing Industry: Testing the Fixed and Random Effect Model on Selected Firms in Ghana - Arthur , Philip (Journal of Asian Business Strategy, 2019)
One of the most complicated fields of financial decision-making is capital structure. Capital structure is the composition of debt and equity capital which involves the funding of a company's assets and can be interpreted as the amount of net value plus preferred stock plus long-term debts. The relationship between capital structure and profitability cannot be underestimated because it is necessary for the company's long-term survivability to improve its profitability. This research sets out to assess the impact of capital structure on the competitiveness of the manufacturing industry in Ghana using some selected firms as the case study for the period between 2005-2012 to provide a critical assessment of the need and value of capital structure. Utilizing a mixed research approach as methodology, thus descriptive statistics and correlation analysis amidst the fixed effect model, the findings revealed that short term debt and long term debt had a negative impact on productivity whilst equity was positively related to profitability. The study recommends that Ghanaian-based manufacturing companies use equity such as retained earnings to expand their business rather than debt financing.